Review of building regulations for safety against hazards in Indian hill towns - Ashwani Kumar (Journal of Urban Management, 2018)
The picturesque hill towns of India are vulnerable to different types of natural hazards, which may cause enormous destruction during their occurrence leading to substantial loss of precious human life and resources. Hill towns are presenting undergoing tremendous developmental activity having densely constructed multi-storied buildings causing severe concerns related to their suitability in the hill towns. Different building regulations are formulated and enforced to the protection of human life and buildings in hill towns. But, in spite of the enforced building regulations, most of the buildings existing in hill towns have no/minimal measures to withstand the adverse impacts of disasters. Therefore, this paper highlights the general issues and problems related to the development and building regulations of hill towns. A comparative study of existing building regulations for safety against natural hazards of various Himalayan hill towns is made to have the in-depth understanding of issues related to building regulations for safety against hazards in hill towns.
Keywords: 710; Urbanization; Building regulations; Disasters; Hill Towns; Seismic vulnerability